The Challenges and Opportunities of Electricity Generation on Economic Growth in South Africa: An ARDL Approach - Hlongwane, Nyiko Worship; Daw, Olebogeng David (International Journal of Energy Economics and Policy, 2022)
This study examines the challenges and opportunities of electricity generation from coal on growth of South African economy. The study utilizes the available annual time series data collected from secondary sources (World Bank) spanning for the period from 1971 to 2015. The study employs the Autoregressive Distributed Lag (ARDL) model and an Error Correction Model (ECM) to analyse the challenges and opportunities of coal-fired electricity generation on growth South African economy. Statistical results from revealed a positive statistically insignificant short run and positive statistically significant long run relationship between electricity generated from coal and economic growth in South Africa. The policy implication from this study is that the policy makers need to acknowledge the positive contribution of coal-fired electricity generation and revise policies on decommissioning of these powerplants. The policymakers should propose and implement policies that encourage coal-fired electricity generation in a way that is environmentally friendly as it boosts economic growth in South Africa.